# Solve for y 1/2=-3/10y-1 12=-310y-1
Rewrite the equation as -310y-1=12.
-310y-1=12
Simplify each term.
Combine y and 310.
-y⋅310-1=12
Move 3 to the left of y.
-3y10-1=12
-3y10-1=12
Move all terms not containing y to the right side of the equation.
Add 1 to both sides of the equation.
-3y10=12+1
Write 1 as a fraction with a common denominator.
-3y10=12+22
Combine the numerators over the common denominator.
-3y10=1+22
Add 1 and 2.
-3y10=32
-3y10=32
Multiply both sides of the equation by -103.
-103⋅(-3y10)=-103⋅32
Simplify both sides of the equation.
Simplify -103⋅(-3y10).
Cancel the common factor of 10.
Move the leading negative in -103 into the numerator.
-103⋅(-3y10)=-103⋅32
Move the leading negative in -3y10 into the numerator.
-103⋅-3y10=-103⋅32
Factor 10 out of -10.
10(-1)3⋅-3y10=-103⋅32
Cancel the common factor.
10⋅-13⋅-3y10=-103⋅32
Rewrite the expression.
-13⋅(-3y)=-103⋅32
-13⋅(-3y)=-103⋅32
Cancel the common factor of 3.
Factor 3 out of -3y.
-13⋅(3(-y))=-103⋅32
Cancel the common factor.
-13⋅(3(-y))=-103⋅32
Rewrite the expression.
-1⋅(-y)=-103⋅32
-1⋅(-y)=-103⋅32
Multiply.
Multiply -1 by -1.
1⋅y=-103⋅32
Multiply y by 1.
y=-103⋅32
y=-103⋅32
y=-103⋅32
Simplify -103⋅32.
Cancel the common factor of 2.
Move the leading negative in -103 into the numerator.
y=-103⋅32
Factor 2 out of -10.
y=2(-5)3⋅32
Cancel the common factor.
y=2⋅-53⋅32
Rewrite the expression.
y=-53⋅3
y=-53⋅3
Cancel the common factor of 3.
Cancel the common factor.
y=-53⋅3
Rewrite the expression.
y=-5
y=-5
y=-5
y=-5
Solve for y 1/2=-3/10y-1

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top